2009
DOI: 10.1097/qad.0b013e328321b75e
|View full text |Cite
|
Sign up to set email alerts
|

CD4 cell-guided scheduled treatment interruptions in HIV-infected patients with sustained immunologic response to HAART

Abstract: The two strategies may be considered clinically equivalent. CD4 cell-guided STIs seem a possible alternative for chronically infected individuals responding to HAART provided that CD4 cell decrements would be steadily maintained above a safe threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
4
35
1
Order By: Relevance
“…Treatment interruption was well tolerated in most participants, in agreement with other therapeutic vaccine and treatment interruption trials. 5,15,19,20 However, one placebo recipient did experience a fatal myocardial infarction during cART interruption, which the investigator could not exclude as possibly related to study participation since previous studies have linked cART interruption to increased levels of infl ammation and increased risk of cardiovascular events; 15 however, the measured infl ammatory marker (high-sensitivity C-reactive protein) was not raised in this case.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Treatment interruption was well tolerated in most participants, in agreement with other therapeutic vaccine and treatment interruption trials. 5,15,19,20 However, one placebo recipient did experience a fatal myocardial infarction during cART interruption, which the investigator could not exclude as possibly related to study participation since previous studies have linked cART interruption to increased levels of infl ammation and increased risk of cardiovascular events; 15 however, the measured infl ammatory marker (high-sensitivity C-reactive protein) was not raised in this case.…”
Section: Discussionmentioning
confidence: 58%
“…20 published reports of clinical trials assessing various HIV therapeutic vaccine approaches, all of which included a "structured" or "analytical" cART interruption phase, were identifi ed. 4,5,11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] These investigations have included various HIV-specifi c peptide approaches delivered either directly or through viral vectors (eg, adenovirus, canarypox, fowl pox, modifi ed vaccinia Ankara), DNA plasmids, or even as peptide loaded dendritic cells. Many of these clinical studies have been done in small sample sizes (ie, ≤30 participants), 19,21,24,26,27,29,33,34,36 and often in a non-controlled manner, 11,21,24,33,34 making defi nitive conclusions diffi cult.…”
Section: Panel: Research In Contextmentioning
confidence: 99%
“…Aiming to maintain CD4 cell counts higher than 350 cells/ and HIV virus loads less than 100,000 copies/ , Ruiz et al designed an experiment to evaluate the safety of CD4 cell and HIV virusguided STIs [13]. Many works have been done to compare the STIs with the continuous antiretroviral therapy (ART), but conflicting results have been reported [7,11,[13][14][15][16][17]. In particular, Maggiolo et al made a conclusion that the structured treatment can result in the similar benefits for the patients with the continuous therapies [7], while the SMART study group found that STIs may also endanger the patients' life if their immune responses are not sufficiently stimulated [18].…”
Section: Introductionmentioning
confidence: 99%
“…Structured treatment interruptions (STIs), the alternative strategies, have been designed to effectively achieve sustained specific immunity for early therapy in HIV infection. Indeed, STIs are beneficial for some chronically infected individuals who may need to take drugs throughout their lives as well as the reconstruction of patients' immune system when they are not taking the drugs [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the LOCF-d analysis, we carried the last value forward for individuals whose data were missing due to skipped visits or administrative dropout. We assumed that other individuals with missing data -those who dropped out for reasons related to efficacy or tolerability -would see a decline in CD4z cell count similar to that seen in randomized trials of structured treatment interruptions [27][28][29] (3 cells/mm 3 per week).…”
Section: Introductionmentioning
confidence: 99%